Pengembangan E-Book Teks Eksposisi Berbasis Aplikasi Canva dengan Model Problem Based Learning untuk Siswa Kelas X MA Tahfizh Al-Habibi - Nafiqah, Putri; Rita, Rita; Safina, Nila (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2024)
This study aimed to develop and assess the feasibility of an e-book on exposition text material enhanced by the Canva application using the Problem-Based Learning (PBL) model for class X students at MA Tahfizh Al-Habibi. Employing the 4D development model by Thiagarajan (1974), which includes Define, Design, Develop, and Disseminate phases, the research involved a population of 60 students with a sample of 20 students from class X-3. Data collection methods included questionnaires, observations, and interviews. The findings indicated that the e-book is highly feasible, with material experts rating its validity at 85.6% and 88.8%, respectively, and design experts at 93%. Trials conducted with teachers and students yielded an overall average score of 87% from the Indonesian language teacher and 96% from students, both categorized as "highly feasible." These results suggest that the e-book on exposition text material assisted by the Canva application using the PBL model is valid and suitable for educational use.